The possible role of liver kinase B1 in hydroquinone‐induced toxicity of murine fetal liver and bone marrow hematopoietic stem cells. Issue 7 (23rd December 2014) - Li, Zhen; Wang, Chunhong; Zhu, Jie; Bai, YuE; Wang, Wei; Zhou, Yanfeng; Zhang, Shaozun; Liu, Xiangxiang; Zhou, Sheng; Huang, Wenting; Bi, Yongyi; Wang, Hong
ABSTRACT: Epidemiological studies suggest that the increasing incidence of childhood leukemia may be due to maternal exposure to benzene, which is a known human carcinogen; however, the mechanisms involved remain unknown. Liver Kinase B1 (LKB1) acts as a regulator of cellular energy metabolism and functions to regulate hematopoietic stem cell (HSC) homeostasis. We hypothesize that LKB1 contributes to the deregulation of fetal or bone hematopoiesis caused by the benzene metabolite hydroquinone (HQ). To evaluate this hypothesis, we compared the effects of HQ on murine fetal liver hematopoietic stem cells (FL‐HSCs) and bone marrow hematopoietic stem cells (BM‐HSCs). FL‐HSCs and BM‐HSCs were isolated and enriched by a magnetic cell sorting system and exposed to various concentrations of HQ (0, 1.25, 2.5, 5, 10, 20, and 40 μM) for 24 h. We found that the inhibition of differentiation and growth, as well as the apoptosis rate of FL‐HSCs, induced by HQ were consistent with the changes in BM‐HSCs. Furthermore, G1 cell cycle arrest was observed in BM‐HSCs and FL‐HSCs in response to HQ. Importantly, FL‐HSCs were more sensitive than BM‐HSCs after exposure to HQ. The highest induction of LKB1 and adenosine monophosphate‐activated protein kinase (AMPK) was observed with a much lower concentration of HQ in FL‐HSCs than in BM‐HSCs. LKB1 may play a critical role in apoptosis and cell cycle arrest of HQ‐treated HSCs. This research has developed innovative ideas concerning benzene‐induced hematopoietic toxicity or embryotoxicity, which can provide a new experimental evidence for preventing childhood leukemia. © 2014 Wiley Periodicals, Inc. Environ Toxicol 31: 830–841, 2016.